New paths to social justice and recovering the past. (2nd July 2016) - Cusack-McVeigh, Holly
ABSTRACT: On April 1, 2014, after months of investigative work and intensive planning, FBI agents knocked on the door of a private collector in rural Indiana. This was the start of a complex, multi-year investigation that resulted in the recovery of several thousand objects of cultural heritage. The collection, noted by scholars and agents alike for its "astounding global and temporal scope, " included material culture from places as diverse as Colombia, China, Peru, Ecuador, Haiti, the Dominican Republic, Mexico, New Zealand, Papua New Guinea, Italy, Canada and the United States. What is most relevant, however, is the way the FBI has handled the case and why it may prove to be a replicable model. This article examines this unique, collaborative approach and its implications for future cases worldwide. It also highlights the moral issues surrounding cultural heritage protection and the shared sense of responsibility that this investigation engendered among stakeholders.